2021
DOI: 10.1016/j.ijso.2021.100333
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nursing self-care educational intervention on depression in women with breast cancer undergoing post-mastectomy chemotherapy: A quasi-experimental study

Abstract: Background and objective: Depression is one of the most common psychological reactions that patients show during diagnosis and treatment. This study aimed to determine the effectiveness of nursing self-care educational intervention on reducing depression in women with breast cancer undergoing post-mastectomy chemotherapy. Methods: This quasi-experimental study (pre-test-post-test) was performed on 90 women with breast cancer undergoing post-mastectomy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[20] Studies based on selfcare training for breast cancer sufferers and similar studies have sometimes been conducted and the results have been different. [22][23][24][25] However, a study that has been conducted on the education of breast cancer patients from palliative care with this focus was not found. Therefore, this research was conducted to investigate the role of palliative care education in improving the life quality of women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Studies based on selfcare training for breast cancer sufferers and similar studies have sometimes been conducted and the results have been different. [22][23][24][25] However, a study that has been conducted on the education of breast cancer patients from palliative care with this focus was not found. Therefore, this research was conducted to investigate the role of palliative care education in improving the life quality of women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have carried out a series of research work to improve the level of perceived control and the QoL of patients with BC, such as psychological education intervention (22)(23)(24)(25)(26), nursing self-care educational intervention (27) and Web/or telephone intervention (28)(29)(30)(31), physical activities (11,(32)(33)(34)(35), the appearance care (36), self-disclosure intervention (37), community based intervention (38). Although these projects have achieved satisfactory results, there are few comprehensive methods including postoperative physical, psychological and social rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Fetaini et al in a study on the impact of BC treatment options including chemotherapy on the QoL demonstrated their negative effects on survivors' physical and psychosocial health [10]. Bouya et al showed that nursing education can positively influence overall QoL and psychological well-being and consequently reduce side effects in women with BC [11]. Identifying factors associated with QoL can help nurses alleviate the symptoms of BC [12].…”
Section: Introductionmentioning
confidence: 99%